Effect of Solution Treatment on Fatigue Crack Propagation Behaviour of Magnesium Alloy - Mohd Daud, Mohd Ahadlin (2010)

(untitled)
An investigation on the effect of solution treatment on fatigue crack propagation (FCP) behaviour of AZ61 magnesium alloy was carried out. A centre cracked plate tension (CCT) specimen was prepared from an extruded cylindrical AZ61 magnesium alloy rod. The solution treatment was performed at 400oC for one hour to get homogeneous solid solution before quench in water. The FCP test was conducted in a laboratory air environment under a constant amplitude sinusoidal loading with a stress ratio of 0.1 and a frequency of 10 Hz. The FCP curve for solution treated samples was then compared to that of the extruded AZ61 magnesium alloy. Results showed that solution treatment shifted the FCP curve to the left and demonstrated a lower fatigue crack propagation resistance at the high stress intensity region. The threshold value was recorded at 0.91 MPa√m.